Benchmarking: applications to transfusion medicine. (31st May 2013) - Heddle, N. M.; Barty, R.
<x xml:space="preserve">Abstract</x> Benchmarking is 'a structured, continuous, collaborative process in which comparisons for selected indicators are used to identify factors which when implemented will improve transfusion practices'. In the Transfusion Medicine literature, there are only a few published articles that meet the criteria for benchmarking: (1) using comparisons between institutions to identify practice variation; (2) using a communication and/or evaluation process to identify factors associated with best practices; (3) introduce best practice factors into one's own setting; and (4) re‐evaluate performance. Three models for benchmarking have been proposed: (1) a regional benchmarking programme that collects and links relevant data from existing electronic sources; (2) a sentinel site model where data from a limited number of sites are collected; and (3) an institutional‐initiated model where a site identifies indicators of interest and approach other institutions as comparators. Finland has the most well‐developed benchmarking model where hospital data are collected electronically from multiple sources and analysed centrally with web‐based reports available for participants. Areas of practice variation are explored in annual benchmarking workshops, interventions are identified and implemented, and the impact of the interventions are evaluated at a later date. A provincial model used in Canada will also be described showing the impact on red cell outdating when hospitals were challenged to meet evidence based targets. Limitations of benchmarking and future research will be discussed.